Time and the Shared World Heidegger on Social Relations - McMullin, Irene (Northwestern University Press, 2012)
This volume challenges the view that Heidegger offers few resources for understanding humanity's social nature. The book demonstrates that Heidegger's reformulation of traditional notions of subjectivity has implications for understanding the nature of relationships. McMullin shows that Heidegger's characterization of selfhood as fundamentally social presupposes the responsive acknowledgment of each person's particularity and otherness. In doing so, she argues that Heidegger's work on the social nature of the self must be located within a philosophical continuum that builds on Kant and Husserl's work regarding the nature of the a priori and the fundamental structures of human temporality, while also pointing forward to developments of these themes found in Heidegger's later work and in such thinkers as Sartre and Levinas. By developing unrecognized resources in Heidegger's work, this volume provides a Heidegger-inspired account of respect and the intersubjective origins of normativity.